Avaliação da ocorrência, expressão e envolvimento do operon pil na aderência de cepas de Escherichia coli enteropatogênica (EPEC) - Castro, Felipe Silva [UNIFESP] (2018)
Enteropathogenic Escherichia coli (EPEC) cause a characteristic intestinal lesion (attaching/effacing lesion) and are identified by the production of the localized adherence pattern (LA) on HeLa cells. On the other hand, enteroaggregative E. coli (EAEC), which are emerging pathogens that can cause persistent diarrhea and that colonize the intestinal mucosa by forming biofilms, produce the aggregative adherence pattern (AA). Our group has previously identified EPEC strains of the O119:H6 serotype that produce a hybrid adherence pattern, i.e., LA and a pattern similar to AA (AAlike) simultaneously (AL/ AAlike +). The horizontal transfer of plasmid pGM80 from an O119:H6 LA/AAlike+ strain to a nonadherent E. coli strain generated AAlike+ transconjugants. This plasmid carries the pil operon, which encodes a variant of Pil, a type IV fimbriae responsible for the AA phenotype in some EAEC strains. In this study, we evaluated the distribution of the pil operon in EPEC strains (22 serotypes, 14 geographic regions, isolated between 1950 and 2015) as well their expression and spreading ability by conjugation. PCR of two previously described pilS alleles (pilSEc404 and pilSC1096), the Pil’s pilin encoded gene, revealed its presence in ~ 54.5% of the 164 analysed strains, with pilSEc404 and pilSC1096 occurring at similar frequencies (~ 30 % and 25%, respectively). The pilSEc404 (76%) and pilSC1096 (46%) alleles were more frequent in O119: H6 and O111:H2, respectively. The pilS + strains were isolated in Chile, Peru and in different Brazilian cities, with the oldest isolated in 1966. There was no absolute relationship between the presence of pilS and the AAlike phenotype in HeLa cells, as this phenotype was also observed in some pilS negative strains, while some LA positive strains showed pilS. Quantitative analyzes of the expression of six essential genes for the assembly of Pil (piLN, pilQ, pilR, pilS, pilU and pilV) by qRTPCR between three LA+ strains and three LA/ AAlike+ strains showed no correlation in the expression of these genes and the AAlike phenotype. The potential involvement of pilV subtypes (which encodes the Pil adhesin) in the AAlike phenotype was also evaluated. In brief, the pil operon was found to occur more frequently in the classical serotypes of EPEC and it was confirmed that the pilV subtypes and specific variations in the adhesin composition of the Pil fimbriae was not related to the formation of the AAlike phenotype in the analysed strains. In addition, a fine regulation of the pil genes is probably necessary for the production of functional Pil fimbriae and the spread of these genes.